Workshop Sistem Informasi Desa Dan Kawasan (SiDeKa) Desa Fatuana, Kecamatan Insana - Kelen, Yoseph Pius Kurniawan; Sikas, Oktovianus (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
Sharing public information is the obligation of public bodies that is mandated by Law No. 14 of 2008 concerningFreedom of Public Information. Public bodies must build and develop systems information and documentation to managepublic information well and efficientlyso that it can be easy for accessed , strengthened again in Law No. 6 of 2014 Article 82(4)which reads the village government must inform planning and implementation Village Medium Term Development Plan,Village Government Work Plan, and Village Revenue and Expenditure Budget to Village communities through informationservicesto the public and report it at the Village Conference at least 1 (one) year once.The purpose of this service is to trainvillage officials to use SiDeKa as a one of the media that can encourage the emergence of four (4) types of noveltynamely:awareness, skills, habits and governance of the Village Information System for village government.This communityservice activity is carried out in three stages. The first stage is a location survey and distribution of ICT understandingquestionnaires at the apparatus levelvillage. The second stage is testing equipment availability and internet network onlocation, and the Third Stage is the SiDeKa workshop for devices Fatuana village. All activities located at the Sekon Villageoffice, Insana Subdistrict. The reality in the location is that there are still many people with minimal knowledge useinformation technology devices related to responsibilities as the village apparatus in documenting all village administrationdata. Head of the village up to the heads of affairs (Kaur) and the accompanying staff of the village of Fatuana face manyproblems related to the lack of computer and internet network facilities and low skills of the ability to use computers incollaborating all village data from various sectors to support development decision making village. This Village and RegionalInformation System (SiDeKa) workshop activity provideshuge benefits for the Fatuana village in organizing the databasecoordinated villages using the help of IT-based systems